KEJADIAN RESISTENSI INSULIN PADA ANAK OBESITAS USIA 9-12 TAHUN DI KOTA SEMARANG - Asnelviana, Hana; Sulchan, Muhammad; Panunggal, Binar (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2017)
Introduction: Obesity is caused by imbalance amount of energy intake and energy requirement of the body. Obesity in children has high risk to become obesity in adult and results in degenerative diseases. In obese children have higher of getting insulinÂ resistance. This study was aimed to determine insulin resistance in obesity children aged 9-12 years in Semarang.Methods: This study used a cross-sectional design with two groups: height below the median-obesity circumference (TBBM-obesity) and height above the median-obesity (TBAM-obesity). Screening was done in 602 children aged 9-12 years in urban and suburban areas of Semarang. Nutritional status was determined with measurements of z-scores of height-for-age (HAZ) and waist circumference. To define insulin resistance were measured using homeostasis model assessment of insulin resistance (HOMA-IR). Data were then analyzed by Mann-Whitney test and Spearman test.Results: There was found 75% subjects with high HOMA-IR value. HOMA-IR value in TBAM-obesity was 42.5% higher than TBBM-obesity was 32.5% (p= 0,088). Waist circumference and Waist to Height Ratio(WHtR) has a correlation on the increased HOMA-IR value (r= 0.662 p=0.000 andÂ r= 0.333 p=0.036) and height does not has a correlation on the increased HOMA-IR value (r=0.235; p= 0.144). Conclusion: Insulin resistance from all subject were found 75%. Waist circumference and Waist to Height Ratio(WHtR) has a correlation on the increased HOMA-IR value and height does not has a correlation on the increased HOMA-IR value.